2022
DOI: 10.3389/fpubh.2022.954264
|View full text |Cite
|
Sign up to set email alerts
|

Economic evaluation of first-line nivolumab plus cabozantinib for advanced renal cell carcinoma in China

Abstract: BackgroundIn the Checkmate9ER trial, first-line treatment with nivolumab combined with cabozantinib (NI + CA) has shown efficacy for advanced renal cell carcinoma. This study aims to evaluate the impact of the health and economic outcomes of NI + CA in China.MethodsClinical efficacy data were derived from pivotal phase III CheckMate 9ER trial. A three-state partitioned survival model was established based on disease progression. Progression-free survival and overall survival of NI + CA vs. sunitinib were fitte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
2
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 31 publications
0
2
0
1
Order By: Relevance
“…15 Wang et al reported that combination therapy with nivolumab and tyrosine kinase inhibitors may increase medical costs and could be less cost-effective in patients with renal cell carcinoma. 27 In patients with melanoma who were administered adjuvant treatment, nivolumab may be more cost-effective than other immune checkpoint inhibitors and molecule-targeted therapies. 22 Furthermore, Kashiwa et al revealed that nivolumab was more cost-effective as a late-line treatment than as a first-line treatment for gastric cancer.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…15 Wang et al reported that combination therapy with nivolumab and tyrosine kinase inhibitors may increase medical costs and could be less cost-effective in patients with renal cell carcinoma. 27 In patients with melanoma who were administered adjuvant treatment, nivolumab may be more cost-effective than other immune checkpoint inhibitors and molecule-targeted therapies. 22 Furthermore, Kashiwa et al revealed that nivolumab was more cost-effective as a late-line treatment than as a first-line treatment for gastric cancer.…”
Section: Discussionmentioning
confidence: 99%
“…Given that ∼90% of medical costs are attributed to medical consultation fees and drugs, especially in the field of oncology, where treatment costs are becoming increasingly expensive, economic evaluation is crucial. The economic impact of nivolumab has been reported for melanoma, lung cancer, gastric cancer, and renal cell carcinoma 18,22–27 . Wang et al.…”
Section: Discussionmentioning
confidence: 99%
“…Следует учитывать и то, что группа благоприятного прогноза мПКР неоднородна по молекулярно-генетическому профилю, и персонализированный подход позволяет выделить пациентов, для которых монотерапия сунитинибом является оптимальным вариантом лечения [25]. Зачастую монотерапия сунитинибом обладает меньшей финансовой нагрузкой и более доступна в клинической практике [32][33][34], а также оставляет больше вариантов для последующих линий терапии 2 .…”
Section: список литературы / Referencesunclassified